THE FITNESS LEVEL OF CBF REFEREES IN A PERIOD OF SEVEN YEARS (Fiep Bulletin - online, 2015)
This study aims at analyzing the level of physical capacity of professional referees for seven years. The population in this study was formed by referees from the Soccer Federeation in Paraná (Federação Paranaense de Futebol), credited by CBF, who presented themselves to the Physical Evaluation Committee from FPF to do the physical capacity tests in 1997, 2000, and 2004. The sample was formed by 24 male referees, and the criteria for selection was the referee's participation in the physical tests in 1997, 2000, and 2004. the battery of tests used was the one indicated by FIFA, that is made of: a 12 minute run (Cooper's test), two 50 m sprint, 200 m sprint, with the two last tests being done alternately. The analysis of the results showed that during the seven-year period there was a decrease both in the aerobic and anaerobic power, and this reduction in the performance could be attributed to the lack of seriousness of the Refereeing Committee at the moment they applied the tests, the fact that the classes for physical preparation were not offered by Association of Referees in Paraná (Associação dos Árbitros do Paraná) anymore, and the lack of a constant physical activity that should be performed by the referees.
Keywords: soccer / football referee; physical condition; physical test; FIFA.